Eating the Dead to Keep Atherosclerosis at Bay - Brophy, Megan L.; Dong, Yunzhou; Wu, Hao; Rahman, H. N. Ashiqur; Song, Kai; Chen, Hong (Frontiers in Cardiovascular Medicine, 2017)
Atherosclerosis is the primary cause of coronary heart disease (CHD), ischemic stroke, and peripheral arterial disease. Despite effective lipid-lowering therapies and prevention programs, atherosclerosis is still the leading cause of mortality in the United States. Moreover, the prevalence of CHD in developing countries worldwide is rapidly increasing at a rate expected to overtake those of cancer and diabetes. Prominent risk factors include the hardening of arteries and high levels of cholesterol, which lead to the initiation and progression of atherosclerosis. However, cell death and efferocytosis are critical components of both atherosclerotic plaque progression and regression yet, few currently available therapies focus on these processes. Thus, understanding the causes of cell death within the atherosclerotic plaque, the consequences of cell death, and the mechanisms of apoptotic cell clearance may enable the development of new therapies to treat cardiovascular disease. Here, we review how ER stress and cholesterol metabolism lead to cell death and inflammation, how dying cells affect plaque progression, and how autophagy and the clearance of dead cells ameliorates the inflammatory environment of the plaque. In addition, we review current research aimed at alleviating these processes and specifically targeting therapeutics to the site of the plaque.